Fat Tuesday fricassee - Cook, J. J. (Cook, J. J. Biscuit Bowl food truck mysteries., 2015)
Mardi Gras. Two weeks of carnival celebrations has got Zoe running ragged. By day, she charms hungry tourists with authentic Southern cuisine. At night, she accompanies her father to one masquerade ball after another, hobnobbing with the high rollers of the secret cabal known as the Mistics of Time. But the fun turns frightening when Zoe stumbles across "Death's" dead body. Journalist Jordan Phillips attended the Mistics' latest bash in a traditional Death costume, and received a fatal bullet wound for the privilege. With more than three hundred masked suspects determined to remain anonymous, and the police covering up the facts behind the murder of the investigative reporter, Zoe realizes the Mistics have some serious secrets to hide.